2017
DOI: 10.1371/journal.pone.0172823
|View full text |Cite
|
Sign up to set email alerts
|

Effects upon metabolic pathways and energy production by Sb(III) and As(III)/Sb(III)-oxidase gene aioA in Agrobacterium tumefaciens GW4

Abstract: Agrobacterium tumefaciens GW4 is a heterotrophic arsenite [As(III)]/antimonite [Sb(III)]-oxidizing strain. The As(III) oxidase AioAB is responsible for As(III) oxidation in the periplasm and it is also involved in Sb(III) oxidation in Agrobacterium tumefaciens 5A. In addition, Sb(III) oxidase AnoA and cellular H2O2 are also responsible for Sb(III) oxidation in strain GW4. However, the deletion of aioA increased the Sb(III) oxidation efficiency in strain GW4. In the present study, we found that the cell mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…7, the results showed that the transcriptional expression levels of most of genes were up-regulated induced by Sb(III) except for arsC. Although the exposure of 0.5h Sb(III) decreased the transcriptional expression levels of arsB_123 and arsB cluster, the expression levels of aioB and arsB_123 were up-regulated after 1h, It has been reported that aioA expression was induced by Sb(III) [11]. Our results showed that expression level of aioB was up-regulated from 1 to 4h compared to uninduced cell, indicating that the aioB gene was induced by Sb(III) and played a putative part in oxidizing Sb(III).…”
Section: Transcriptional Expression Analysis In Bacillus Sp S3 With mentioning
confidence: 84%
See 1 more Smart Citation
“…7, the results showed that the transcriptional expression levels of most of genes were up-regulated induced by Sb(III) except for arsC. Although the exposure of 0.5h Sb(III) decreased the transcriptional expression levels of arsB_123 and arsB cluster, the expression levels of aioB and arsB_123 were up-regulated after 1h, It has been reported that aioA expression was induced by Sb(III) [11]. Our results showed that expression level of aioB was up-regulated from 1 to 4h compared to uninduced cell, indicating that the aioB gene was induced by Sb(III) and played a putative part in oxidizing Sb(III).…”
Section: Transcriptional Expression Analysis In Bacillus Sp S3 With mentioning
confidence: 84%
“…S3 and other comparative strains renders clues about the genomic plasticity of these isolates (Table S8) Signatures of HGT events generally could be facilitated by MGEs, such as integration sites, anomalous GC contents, or varied codon usage, suggesting that the potential contributor of the observed genomic rearrangements between the genomes of genus Bacillus [51]. MGEs were key driving forces of genome evolution [11], indicating that high genomic plasticity in Bacillus genus was extended to potential strategies to cope with high metal(loid) ion concentrations of their natural habitats. Genomic island (GEIs), which have been committed to provide antibiotic resistance to the host bacteria, were generally divided into 4 categories based on their function, including resistance island (RIs), virulence genes, metabolic islands, and symbiotic island(SIs) [52].…”
Section: Mobile Gene Elements In Bacillus Genomesmentioning
confidence: 99%
“…The results showed that the majority of MGEs were distributed on chromosomes within the Bacillus genus. MGEs were key driving forces of genome evolution and played a pivotal role in HGT events [11], indicating that high genomic plasticity in Bacillus genus was extended to potential strategies to cope with high metal (loid) ion concentrations of their natural habitats. GEIs, which have been committed to provide antibiotic resistance to the host bacteria, were generally divided into 4 categories based on their function, including resistance island (RIs), virulence genes, metabolic islands, and symbiotic island (SIs) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Antimony (Sb) is a toxic metalloid in group 15 of the periodic table of elements and excessive Sb can cause harmful damages to the human health [1,4]. Sb and its compounds therefore have been listed as priority pollutants by the United States Environmental Protection Agency (USEPA) and the European Union (EU) [7,11]. The maximum acceptable concentration of Sb in drinking water has been set at 6 μg/L by the World Health Organization (WHO) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transcriptional regulator ArsR and arsenite reductase ArsC were also found to be involved in the As(III)/Sb(III) resistance (Table 6 ) [ 32 34 ]. Recently, it has been reported that an oxidoreductase AnoA, which belongs to the short-chain dehydrogenase/reductase family, and catalase KatA, which is responsible for H 2 O 2 degradation, are all involved in bacterial Sb(III) oxidation/resistance in 10.1601/nm.1311 GW4 [ 35 38 ]. One AnoA homologue oxidoreductase gene and five catalase genes were identified in the genome of strain CY1 T (Table 6 ), which may associate with Sb(III) oxidation/resistance.…”
Section: Insights From the Genome Sequencementioning
confidence: 99%